PENINGKATAN KETERAMPILAN MENULIS CERITA PENDEK BERBANTUAN MEDIA AUDIO VISUAL TRAILER FILM ASING SISWA KELAS X. 1 SMAN 2 PADANGPANJANG - Megasari Martin; Hasanuddin WS; Ermanto . (Bahasa, Sastra, dan Pembelajaran, 2013)
Abstract: Writing is one language skills at High School. Based on the observation, the found that’s students faced a problem in how to express their mind and their idea to tell their experience in writing short story. It is seen from the results of students learning to write short stories not reach the minimum completeness criteria values. Suspected this was ave to the learning factors that are less attractive to students. This classroom research aims to (1) describe improving student in writing a short story with  using audio visual trailer movie, (2) describe result student in writing a short story with  using audio visual trailer movie. This research is this classroom action research. This research in conducted in two cycles. Each cycles goes through some steps: planning, acting/implementating, observating, reflecting. This classroom research aims to describe improving student in writing a short story at Class X.1 of Senior High School 2 Padangpanjang by audio visual movie trailer. The data of the research were qualitative data from observation using the observation sheets, field note, and quantitative data as such a student test performance assessment. The research findings are: (1) there is an increase in activity of students during the learning process in the first cyle and second cyle, audio visual aided movie trailer, it is evident from the observations collaborators, (2) there is an in students learning outcomes in writing short story, from precyle average only 66 to 35% the percentage of completeness, first cyle in increased to 75 with 74% percentage of completeness, and the second cyle the average value being 83 with a percentage of 94% completeness. Keywords :keterampilan menulis, cerita pendek, media audio visual trailer film asing